OFFRED RESISTANCE AGAINST OPPRESSION IN MARGARETT ATWOOD’S THE HANDMAID’S TALE - SKOLASTIKA ARTAULI MAHA SIHARINGGITAN SITOEMORANG (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Oppression is the inequitable use of authority, law, or physical force to prevent others from being free or equal.Feminist fight against the oppression of women.Women have been unjustly held back from achieving full equality for much of human history in many societies around the world.This study aims to analyze the resistance against oppression of Offred as the main character in Margarett Atwood’s novel The Handmaid’s Tale.in order to analyze the text,This study uses Kate Millet’s theory on sexual politics.The analysis finds out that are two ways Offred become a radical person.Firsty because Gilead Society restrict freedom of the Handmaid , and secondly Gilead Society uses the Handmaid body as a device of the country to produced a baby. And that reasons make Offred shows her own resistance in the end.